Labour market flexibility v. job security – a comparative analysis of Swiss and Polish labour law regulations on fixed-term employment contracts - Ludera-Ruszel, Agata (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2015)
In the time of a knowledge-based economy, flexibility has become increasingly important for both employers and employees. The process of making the labour market flexible leads to the greater popularity of atypical forms of employment, with fixed-term employment contracts among them, which are considered to be less consistent with the protective function of labour law in comparison with indefinite- term employment contracts. The right balance between labour market flexibility and job security has become a real concern. Taking into account the legal regulations on fixed-term employment contracts which are now in force in Poland and Switzerland, this paper determines how that relationship has been shaped in those countries with reference to fixed-term employment contracts.

W dobie gospodarki opartej na wiedzy, elastyczność staje się istotna dla pracodawcy i pracownika. Dążenie do większej elastyczności na rynku pracy powoduje wzrost popularności atypowych form zatrudnienia, w tym także umowy o pracę na czas określony, które jednak są uważane za mniej bezpieczną formę zatrudnienia w porównaniu do umowy o pracę na czas nieokreślony. W tych warunkach istotnym wyzwaniem staje się zachowanie właściwej równowagi między elastycznością rynku pracy a bezpieczeństwem zatrudnienia. Opierając się na analizie regulacji prawnych o umowie o pracę na czas określony obowiązujących w Polsce i w Szwajcarii, przedmiotem niniejszego artykułu jest ustalenie jak powyższy stosunek został ukształtowany w odniesieniu do umowy o pracę na czas określony.
Elastyczność rynku pracy vs. bezpieczeństwo zatrudnienia – analiza porównawcza polskich i szwajcarskich regulacji prawa pracy w zakresie umowy o pracę na czas określony
Keywords: flexibility; job security; fixed-term employment contract; Poland; Switzerland; elastyczność; bezpieczeństwo zatrudnienia; umowa o pracę na czas określony; Polska; Szwajcaria